Effectiveness of Video Assisted Teaching Programme on Level of Knowledge and Attitude Regarding Prenatal Genetic Testing among Antenatal Mother - C Muthulakshmi; M Kousalya (Wolters Kluwer Medknow Publications, 2024)
Background: Prenatal genetic testing is done throughout pregnancy to identify or diagnose birth defects. These tests aim to help families make educated decisions regarding pregnancy and reproduction, as well as aid healthcare providers in providing optimal care for pregnant women. Prenatal blood screening is performed twice during pregnancy. Aim: The present study aims to assess the Effectiveness of video assisted teaching programme on level of knowledge and attitude regarding prenatal genetic testing among antenatal mother. Materials and Methods: A Quasi experimental, one group pre and post experimental research design was used for this study. The study conducted in SMCH. A total of 60 study participants were recruited by using a non probability convenient sample technique, based on inclusion criteria. Results: The analysis revealed that most of the antenatal mothers, 24 (40%) were aged between 21 and 25 years, 33 (55%) had higher secondary education, 34 (56.6%) were private employees, 43 (71.6%) were Hindus, 46 (76.7%) were residing in urban area, 40 (66.6%) had an income of between INR 10,000 and 20,000, and 48 (80%) and 3 (30%) had friends/relatives and health care professionals as source of information. Conclusion: The study found that video education on genetic testing improved patients' and increased quality of life.